Advances in chemical physics : Volume 146 : Experiments and theories, single molecule biophysics / [electronic resource] - Komatsuzaki, Tamiki (Hoboken, N.J. : Wiley-Blackwell ; Chichester : John Wiley [distributor], 2012)
"Discover the experimental and theoretical developments in optical single-molecule spectroscopy that are changing the ways we think about molecules and atoms -- The Advances in Chemical Physics series provides the chemical physics field with a forum for critical, authoritative evaluations of advances in every area of the discipline. This latest volume explores the advent of optical single-molecule spectroscopy, and how atomic force microscopy has empowered novel experiments on individual biomolecules, opening up new frontiers in molecular and cell biology and leading to new theoretical approaches and insights. Organized into two parts -- one experimental, the other theoretical -- this volume explores advances across the field of single-molecule biophysics, presenting new perspectives on the theoretical properties of atoms and molecules. Single-molecule experiments have provided fresh perspectives on questions such as how proteins fold to specific conformations from highly heterogeneous structures, how signal transductions take place on the molecular level, and how proteins behave in membranes and living cells. This volume is designed to further contribute to the rapid development of single-molecule biophysics research."--Provided by publisher.
Developments on Single-Molecule Experiments. Staring at a Protein: Ensemble and Single-Molecule Investigations on Protein-Folding Dynamics / Satoshi Takahashi, Kiyoto Kamagata -- Single-Molecule FRET of Protein-Folding Dynamics / Daniel Nettels, Benjamin Schuler -- Quantitative Analysis of Single-Molecule FRET Signals and its Application to Telomere DNA / Kenji Okamoto, Masahide Terazima -- Force to Unbind Ligand-Receptor Complexes and the Internal Rigidity of Globular Proteins Probed by Single-Molecule Force Spectroscopy / Atsushi Ikai, Rehana Afrin, Hiroshi Sekiguchi -- Recent Advances in Single-Molecule Biophysics with the Use of Atomic Force Microscopy / Masaru Kawakami, Yukinori Taniguchi -- Dynamical Single-Molecule Observations of Membrane Protein Using High-Energy Probes / Yuji C Sasaki -- Single-Molecular Gating Dynamics for the KcsA Potassium Channel / Shigetoshi Oiki, Hirofumi Shimizu, Masayuki Iwamoto, Takashi Konno -- Static and Dynamic Disorder in Reconstituted Receptor-Adaptor Interaction / Hiroaki Takagi, Miki Morimatsu, Yasushi Sako -- Developments on Single-Molecule Theories and Analyses. Change-Point Localization and Wavelet Spectral Analysis of Single-Molecule Time Series / Haw Yang -- Theory of Single-Molecule FRET Efficiency Histograms / Irina V Gopich, Attila Szabo -- Multidimensional Energy Landscapes in Single-Molecule Biophysics / Akinori Baba, Tamiki Komatsuzaki -- Generalized Michaelis-Menten Equation for Conformation-Modulated Monomeric Enzymes / Jianlan Wu, Jianshu Cao -- Making it Possible: Constructing a Reliable Mechanism from a Finite Trajectory / Ophir Flomenbom -- Free Energy Landscapes of Proteins: Insights from Mechanical Probes / Zu Thur Yew, Peter D Olmsted, Emanuele Paci -- Mechanochemical Coupling Revealed by the Fluctuation Analysis of Different Biomolecular Motors / Hiroaki Takagi, Masatoshi Nishikawa.
Includes bibliographical references and index.
Print version record.
Keywords: Biomolecules; Biophysics; Chemistry, Physical and theoretical; Biomolecules; Biophysics; Chemistry, Physical and theoretical; Molecular Biology; Biophysical Phenomena; Biochemical Phenomena; Electronic resource; Electronic books